The Children's Garden : growing food in the city - Schaefer, Carole Lexa (Little Bigfoot, an imprint of Sasquatch Books, 2017)
Youngsters explore the sights, smells, sensations, and tastes of growing their own food in a community garden. Story based on the Children's Garden in Seattle.